2011
DOI: 10.1186/1758-907x-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of small interfering RNA 3'-end overhangs on chemosensitivity to thymidylate synthase inhibitors

Abstract: BackgroundSmall interfering RNAs (siRNAs) are double-stranded RNAs that effectively inhibit expression of its complimentary target mRNA. Standard siRNAs contain two nucleotide overhangs on their 3' end. While these overhangs are usually comprised of deoxythymidines (dT), it has been shown that any nucleotide can be used on the 3' end without affecting RNAi silencing.ResultsIt was recently shown that extension of the 3' end to five or eight dT molecules allows siRNAs to be effectively complexed with linear poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…After transfection of TS6-dU/dA, antisense strand targeting was maintained, whereas sense strand targeting was significantly reduced. This finding suggests that the 3′-end dU modification interferes with incorporation of the sense strand into RISC and provides an explanation for the slightly greater knockdown of TS previously observed with this ssiRNA (17). Transfection of the modified ssiRNA TS6-FdU/dA resulted in similar strand selection as with TS6-dU/dA.…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…After transfection of TS6-dU/dA, antisense strand targeting was maintained, whereas sense strand targeting was significantly reduced. This finding suggests that the 3′-end dU modification interferes with incorporation of the sense strand into RISC and provides an explanation for the slightly greater knockdown of TS previously observed with this ssiRNA (17). Transfection of the modified ssiRNA TS6-FdU/dA resulted in similar strand selection as with TS6-dU/dA.…”
Section: Resultsmentioning
confidence: 61%
“…We had previously shown that the activity of siRNAs with extended complementary 3′-end overhangs [termed ‘sticky’ siRNAs or ssiRNAs (20)] was at least equivalent or perhaps slightly more effective than standard siRNAs with respect to target mRNA suppression (17). However, in these studies, we determined that the extended dT overhangs on the ssiRNA were degraded, resulting in rescue from the cytotoxic effects of a TS-targeted ssiRNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations